Peningkatan Hasil Belajar Siswa pada Materi Warisan Budaya Kelas VI SD Negeri 2 Joho melalui Penerapan Model Teams Games Tournament (TGT) berbasis Teknologi - Wardani, Shinta Ayu; Sari, Tria Aprilia Ratna; Sari, Aprilia Dita Puspita; Rahmadiana, Ulfa Putri; Ash., Zulvia Rifqi Nabilla; Permana, Erwin Putera; Anam, Misbahul (Jurnal Simki Postgraduate, 2025)
This study aims to improve the academic achievement of 6th grade students at SD Negeri 2 Joho in science lessons on cultural heritage, using the technology-based Teams Games Tournament (TGT) learning model. This study was implemented through the Classroom Action Research (CAR) method which was carried out in two cycles. Each cycle consists of the stages of planning, implementation, observation, and reflection. In the first cycle, learning was carried out using the lecture method, while in the second cycle the TGT model was applied which utilized technology media. The results of the study showed a significant increase in students' average scores, from 62.08 with a completion rate of 41.67% in the first cycle to 77.92 with a completion rate of 83.33% in the second cycle. Thus, the application of the technology-based TGT learning model has proven effective in improving learning outcomes and student participation during learning.